Photo-Induced Spin Dynamics in Semiconductor Quantum Wells - Miah, M Idrish (Springer, 2009)
We experimentally investigate the dynamics of spins in GaAs quantum wells under applied electric bias by photoluminescence (PL) measurements excited with circularly polarized light. The bias-dependent circular polarization of PL (P(PL)) with and without magnetic field is studied. TheP(PL)without magnetic field is found to be decayed with an enhancement of increasing the strength of the negative bias. However,P(PL)in a transverse magnetic field shows oscillations under an electric bias, indicating that the precession of electron spin occurs in quantum wells. The results are discussed based on the electron–hole exchange interaction in the electric field.